Promoting insight into delusions: Issues and challenges in therapy. (1st June 2020) - Kumar, Devvarta
Abstract: During recent years, the role of non-pharmacological interventions in the management of psychotic symptoms, including delusions, has received increased recognition. However, a few factors such as the client's cognitive impairments and poor insight into the illness may create challenges for the therapist in conducting these interventions. Present paper discusses some of these issues and the steps a therapist can take to deal with them.